2014
DOI: 10.4236/ajac.2014.58059
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Degradation of Triazine Herbicides in Water by Photo-Fenton Process

Abstract: In this work, the degradation of 2-chloro-4,6-diamino-1,3,5-triazine in aqueous solutions by photo-Fenton process has been investigated. The preliminary results have shown that the degradation of 2-chloro-4,6-diamino-1,3,5-triazine by photo-Fenton process is more rapid and more effective than Fenton and UV/H2O2 processes. The effects of certain experimental parameters on kinetics and efficiency of the degradation of 2-chloro-4,6,-diamino-1,3,5-triazine by photo-Fenton process, have been evaluated. Under optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Toxicity tests showed that the partial mineralization may be responsible for the presence of degradation products which can be either more toxic than the original dye or may be further degraded to nontoxic products. The degradation of 2-chloro-4,6-diamino-1,3,5-triazine and of cyanuric acid by photo-Fenton process have been reported by Dbira et al 41 . It was observed that that the degradation of these compounds by photo-Fenton process is faster and effective than Fenton and UV/H 2 O 2 processes.…”
Section: Homogeneous Fenton and Photo-fenton Processesmentioning
confidence: 80%
“…Toxicity tests showed that the partial mineralization may be responsible for the presence of degradation products which can be either more toxic than the original dye or may be further degraded to nontoxic products. The degradation of 2-chloro-4,6-diamino-1,3,5-triazine and of cyanuric acid by photo-Fenton process have been reported by Dbira et al 41 . It was observed that that the degradation of these compounds by photo-Fenton process is faster and effective than Fenton and UV/H 2 O 2 processes.…”
Section: Homogeneous Fenton and Photo-fenton Processesmentioning
confidence: 80%
“…Fenton and photo-Fenton reactions are strongly pH-dependent as reported in the literature [40][41][42][43]. Especially, it is well reported that the initial pH conditions significantly influence the production of hydroxyl radicals [20,[43][44][45][46]. To examine the effect of initial pH on the treatment of aqueous solutions containing 100 mg/L of 4EP by the heterogeneous photo-Fenton process, the initial pH values was varied in the range between 3 and 9 using 1000 mg/L H 2 O 2 and 40 mg/L Fe 3 O 4 at room temperature and a stirring rate under 300 rpm.…”
Section: Detailed Onvestigations Of the Degradation Of 4ep By The Hetmentioning
confidence: 81%
“…Particularly, advanced oxidation processes (AOPs) showed high potential to degrade various bioresistant and hazardous organic pollutants in water [18][19][20]. These processes are capable of mineralizing several types of organic pollutants, including phenols, polyphenols, pesticides, pharmaceuticals, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at a pH higher than 3.2, the formation of ferric hydroxide complexes Fe(OH) 3 and the auto-decomposition of H 2 O 2 to oxygen and water reduces the generation of hydroxyl radicals, which decreases the degradation efficiency of DAP. Additionally, the formation of Fe(III)-complexes at high pH values limits the regeneration of ferrous ion (Fe 2+ ) catalyst and then reduces the regeneration of hydroxyl radicals [24,25]. Several studies have reported that pH can dramatically affect the degradation of organic pollutants such as phenols, dyes, and petrochemicals by Fenton oxidation.…”
Section: Influence Of Initial Phmentioning
confidence: 99%